2014
DOI: 10.1589/jpts.26.1679
|View full text |Cite
|
Sign up to set email alerts
|

Relationship among Ocular Diseases, Developmental Levels, and Clinical Characteristics of Children with Diplegic Cerebral Palsy

Abstract: [Purpose] The aim of this study was to evaluate the relationships among vision problems, developmental levels, upper extremity functions, and qualities of life of children with cerebral palsy (CP). [Subjects] The study included 32 children, aged 4–15 years, diagnosed with diplegic type CP. [Methods] Hand function was evaluated using the Manual Ability Classification System (MACS) and the Bimanual Fine Motor Function (BFMF) scale, and the severity of CP was assessed using the Gross Motor Function Classification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…An impairment of such functions in patients with CVI has been widely investigated [ 8 , 56 , 57 ] and may reflect dysfunctions in the oculomotor system and/or in the dorsal stream pathway involved in ocular movements and visually guided actions [ 5 , 8 , 56 , 58 , 59 , 60 ]. Nevertheless, most previous studies have characterized oculomotor dysfunction in children with CVI, mainly focusing on the presence of strabismus and/or nystagmus [ 26 , 32 , 61 ] or on the description of possible visual disorders in CP [ 2 , 5 ]. To our knowledge, only a few clinical and qualitative characterizations of these features have been performed [ 2 , 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…An impairment of such functions in patients with CVI has been widely investigated [ 8 , 56 , 57 ] and may reflect dysfunctions in the oculomotor system and/or in the dorsal stream pathway involved in ocular movements and visually guided actions [ 5 , 8 , 56 , 58 , 59 , 60 ]. Nevertheless, most previous studies have characterized oculomotor dysfunction in children with CVI, mainly focusing on the presence of strabismus and/or nystagmus [ 26 , 32 , 61 ] or on the description of possible visual disorders in CP [ 2 , 5 ]. To our knowledge, only a few clinical and qualitative characterizations of these features have been performed [ 2 , 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the impact of visual impairment associated with cerebral palsy to the quality of life, Boyaci et al [19] found no significant correlations between the quality of life and fundus pathology or strabismus. However, they did not assessed the visual acuity.…”
Section: Discussionmentioning
confidence: 99%
“…GMFCS and BFMF scores correlate with each other. 13 It raises the question whether VI could also be associated with functional classification in children with CP which would be of practical clinical importance.…”
Section: Introductionmentioning
confidence: 99%